RISK FACTOR FOR NEAR MISS AND MATERNAL MORTALITY AT TEACHING HOSPITAL MAKASSAR CITY PERIOD OCTOBER 2018-OCTOBER 2019 - Wibisono, Stefannus; Tahir, Mardiah; S Riu, Deviana; Hamid, Firdaus; Malinta, Umar; Padjalangi, Nursanty (International Journal of Psychosocial Rehabilitation, 2020)
Maternal near miss has similar characteristics to the incidence of maternal death. Women who experience maternal near miss events can provide accurate information that describes the situation during pregnancy, childbirth, and postpartum complications. By examining near-miss events, information about risk factors and factors that need to be avoided can be identified so that it does not cause death. This study aims to assess the effect of labor risk factors on near misses and maternal mortality. The method is a hospital-based case control study to assess risk factors for near misses and maternal mortality. Data is taken from all mothers giving birth above 20 weeks of pregnancy who experienced near misses and maternal deaths in the education network hospital Department of Obstetrics and Gynecology, Faculty of Medicine, Hasanuddin University, Makassar. A total sample of 76 people for inclusion criteria and 76 people as controls, namely mothers giving birth with mild to moderate complications. Controls were selected according to age and hospital for the same inclusion criteria. Data were collected using a questionnaire and analyzed logistic regression with SPSS. The results show there were 67 near-miss events and 9 maternal deaths from 10 October 2018 to 9 October 2019. Logistic regression analysis found that there was an influence of poor nutritional status (p <0.001), pre-existing disease (p <0.001), preterm gestational age (p <0.001), mode of delivery SSTP (p <0.001), less ANC visit (p <0.001), low level of education (p <0.001), and low socio-economic (p 0.01) for near miss and maternal mortality. This study concludes there is a relationship between poor nutritional status, pre-existing disease, preterm gestational age, mode of delivery SSTP, fewer ANC visits, low level of education, and low socio-economic status towards the incidence of near misses and maternal death.